Benzodiazepine inhibits anxiogenic-like response in cocaine or ethanol withdrawn planarians. Issue 6 (September 2016) - Nayak, Sunil; Roberts, Adam; Bires, Kristofer; Tallarida, Christopher S.; Kim, Erin; Wu, Michael; Rawls, Scott M.
Abstract : Planarians spend less time in light versus dark environments. We hypothesized that planarians withdrawn from cocaine or ethanol would spend even less time in the light than drug-naive planarians and that a benzodiazepine would inhibit this response. Planarians pretreated in cocaine or ethanol were placed at the midline of a Petri dish containing spring water that was split evenly into dark and light compartments. Planarians withdrawn from cocaine (1, 10, 100 μmol/l) or ethanol (0.01%) spent less time in the light compartment than water controls; however, this withdrawal response to cocaine (100 μmol/l) or ethanol (0.01%) was abolished by clorazepate (0–100 μmol/l). These data suggest that planarians, similar to rodents, show benzodiazepine-sensitive, anxiogenic-like responses during cocaine or alcohol withdrawal.